Norwegian Approach to Private Internal Investigations: An Empirical Study of Mandates for Fraud Examiners - Gottschalk, Petter (International criminal justice review, 2019)
This article applies principal-agent relationship theory through an empirical study of private investigators’ mandates for fraud examiners in Norway. The business of private internal investigations by external fraud examiners has grown remarkably in the recent decades. Law firms and auditing firms are hired by private and public organizations to reconstruct the past when there is suspicion of misconduct and potential financial crime. Most reports of investigation are kept secret to the public and often also to the police, even when there is evidence of financial crime by white-collar criminals. For this study, we were able to identify and retrieve a total of 49 investigation reports in Norway for the 10-year period from 2006 to 2016. Reports are studied in terms of mandates defining the motive, purpose, scope, tasks, and goals. We find that mandates are deficient, thereby opening up for opportunistic behavior by both parties in the principal-agent relationship.